KESIAPSIAGAAN MASYARAKAT KOTA PADANG DALAM MENGHADAPI RESIKO BENCANA GEMPA DAN TSUNAMI BERBASIS KEARIFAN LOKAL (Studi Kesiapsiagaan Terhadap Resiko Bencana) - Alhadi, Zikri; Sasmita, Siska (Humanus, 2014)
This article aims to describe the research findings about the local community disaster preparedness based on local values in facing the risk of earthquake and tsunami. The authors describe the disaster preparedness of a community with high level of homegenity, since the activity of disaster preparedness for highly homogenic community is very crucial due to to the high population. Beside that, intervention in highly homogenic community is relatively easier in short term because of their uniformed background. The authors also identify the community’s values that can be used as a basis in strengthening community preparedness. Local values include the following: strengthening the role of ‘niniak mamak’, increasing the attendance in the mosque, prayer and ‘ciloteh Lapau’ (conversations in stalls). The result of this study is expected to become the basis for stakeholders in the city of Padang in formulating comprehensive disaster management policies, particularly pre-disaster management. Keywords: disaster, risk preparedness, local values